3D bioprinting of hydrogel‐based biomimetic microenvironments. Issue 5 (3rd December 2018) - Luo, Yongxiang; Wei, Xiaoyue; Huang, Peng
Abstract: Three‐dimensional (3D) bioprinting is a promising technology to produce cell‐laden constructs via patterning living cells, biological factors and biomaterials in a precisely controlled manner. However, it is still a challenge to fabricate human tissues/organs with biological functions for clinical application via 3D bioprinting. Several key issues should be carefully addressed to overcome this challenge, specifically the construction of biomimetic microenvironments. 3D printing has been broadly demonstrated the ability to create structures mimicking native tissues, while it also has the capability to produce biomimetic microenvironments. Therefore, this review will give an overview of the current advances in the art of building and controlling hydrogel‐based biomimetic microenvironments in cells‐laden 3D bioprinting, which are classified by their physical, chemical, and biological features. In the end, we will elaborate the outlook of 3D bioprinting of biomimetic microenvironment. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1695–1705, 2019.